Ni(ii)-Dithiocarbamate and -diphosphine coordination complexes as pre-catalysts for electrochemical OER activity - Pal S.K.; Ansari T.; Yadav C.L.; Singh N.; Lama P.; Indra A.; Kumar K. (My University, 2025)
Electrochemical water oxidation holds immense potential for sustainable energy generation, splitting water into clean-burning hydrogen and life-giving oxygen. However, a key roadblock lies in the sluggish nature of the oxygen evolution reaction (OER). Finding stable, cost-effective, and environmentally friendly catalysts with high OER efficiency is crucial to unlock this technology's full potential. Here, we have synthesized four new cationic heteroleptic Ni(ii) complexes having the formula [Ni(S^S)(P^P)]PF6 (1-4) where S^S represents bidentate dithiocarbamate ligands (N,N-bis(benzyl)dithiocarbamate and N-benzyl-N-3-picolyldithiocarbamate) and P^P represents diphosphine ligands (1,2-bis(diphenylphosphino)ethane (dppe) and 1,1-bis(diphenylphosphino)ferrocene (dppf)). The complexes were characterized by UV-Vis, FT-IR, and multinuclear NMR spectroscopic techniques. Single crystal X-ray structures of all complexes are also reported. The molecular structures showed a distorted square planar geometry around the Ni(ii) center defined by a bidentate S^S dithiolate chelating ligand and a P^P diphosphine chelating ligand. Interestingly, the complexes exhibit weak non-covalent interactions, contributing to the overall supramolecular structures. The role of complexes in water oxidation has been investigated electrochemically in a 1.0 M KOH solution after immobilization onto the surface of activated carbon cloth (CC). Detailed analyses revealed that the complexes are promising precatalysts for generating active Ni(OH)2/NiO(OH) as a true oxygen evolution reaction (OER) catalyst at CC upon anodic activation. Notably, the catalyst derived from complex 4@CC exhibited the highest OER activity with a Tafel slope of 93 mV per decade and reaching a current density of 10 mA cm−2 at a low overpotential of 250 mV in a 1.0 M KOH solution. This study reveals the significance of dithiocarbamate and diphosphine ligands in facilitating the conversion of Ni(ii) complexes into highly active OER catalysts. © 2025 The Royal Society of Chemistry.